Medical documentation, bioanalytical evidence of an accidental human exposure to sulfur mustard and general therapy recommendations. (26th February 2016) - Steinritz, Dirk; Striepling, Enno; Rudolf, Klaus-Dieter; Schröder-Kraft, Claudia; Püschel, Klaus; Hullard-Pulstinger, Andreas; Koller, Marianne; Thiermann, Horst; Gandor, Felix; Gawlik, Michael; John, Harald
Highlights: The vesicant sulfur mustard (SM) is a banned chemical warfare agent. 3 patients were accidentally exposed to SM vapor developing erythema and blisters. Bioanalytical mass spectrometry-based methods allowed verification of exposure. Full recovery was observed under symptomatic therapy on day 56 after exposure. General recommendations for therapy and management of poisoning are given. Abstract: Sulfur mustard (SM) is a chemical warfare agent (CWA) that was first used in World War I and in several military conflicts afterwards. The threat by SM is still present even today due to remaining stockpiles, old and abandoned remainders all over the world as well as to its ease of synthesis. CWA are banned by the Chemical Weapons Convention (CWC) interdicting their development, production, transport, stockpiling and use and are subjected to controlled destruction. The present case report describes an accidental exposure of three workers that occurred during the destruction of SM. All exposed workers presented a characteristic SM-related clinical picture that started about 4 h after exposure with erythema and feeling of tension of the skin at the upper part of the body. Later on, superficial blister and a burning phenomenon of the affected skin areas developed. Similar symptoms occurred in all three patients differing severity. One patient presented sustained skin affections at the gluteal region while another patient came up with affections of the axilla and genital region. Fortunately, full recovery was observed on day 56 after exposure except some little pigmentation changes that were evident even on day 154 in two of the patients. SM-exposure was verified for all three patients using bioanalytical GC MS and LC MS/MS based methods applied to urine and plasma. Urinary biotransformation products of the β-lyase pathway were detected until 5 days after poisoning whereas albumin-SM adducts could be found until day 29 underlining the beneficial role of adduct detection for post-exposure verification. In addition, we provide general recommendations for management and therapy in case of SM poisoning.